Inklusi Keuangan Melalui Literasi Keuangan, Modal Sosial, dan Teknologi Finansial: Desa Blang Kecamatan Syamtalira Aron Kabupaten Aceh Utara - Bustami, Koko; Saifrizal, Muhammad; Inuzula, Lakharis (Journal of Comprehensive Science, 2025)
In this era of digitalization, the development of technology is so rapid, we can feel this from the ease of all jobs that used to be very complex, such as the existence of financial inclusion systems and financial technology, namely banks or e-banking. Banks play an important role for society, this has proven to be a brilliant solution in financial transactions and transfers. So in this case, the role of financial literacy, financial technology and social capital is very important to increase financial inclusion. This study aims to see how the influence of financial literacy on financial inclusion, the influence of social capital on financial inclusion, and financial technology on the financial inclusion of the people of Blang Village". The research method was quantitative with library research data collection techniques and questionnaire distribution. The population of 300 local people with a percentage of relaxation of 5%, sampling using the Slovin formula so that it became 171 respondents. The sampling technique uses a purposive sampling technique with the criteria of productive age of 20 to 40 years who use financial services and live in Blang Village. Data analysis uses descriptive and multiple linear regression. The results of partial financial literacy have no effect on financial inclusion with a tcal value of 1,715 smaller than ttable 1,794 (1,715<1,974). social capital, affecting financial inclusion with a tcal value of 5,293 greater than ttable (5,293>1,974). financial technology has an effect on financial inclusion with a tcal value of 4,235 greater than ttable (4,235>1,974), a simultaneous hypothesis that there is an influence of financial literacy, social capital and financial technology on financial inclusion with a fcal value of 100,393 greater than ftable 2.66 (100,393>2.66).